Linear motor control of headset position for disabled people - Leong, Melissa Sze En (2019)
In a previous Final Year Project (FYP), a Virtual Reality (VR) system has been designed such that the physically disabled people are able to navigate the computer using their eyes. Consisting of a gaze-tracking software and a VR headset, the software reads user eye movement and translates it to cursor and virtual keyboard movement on the computer, which will be projected through the VR headset. As the intended user of the product is a disabled user, they require additional help to physically adjust the position of the VR headset on their faces should it be uncomfortable for them. This project thus aims to study how to automate this process, by allowing the users to “adjust the headset on their own” using the gaze-tracking software and an external motor. In this project, a few motors were considered and studied, and a prototype for a two-axis motor was built with micro servos and Arduino Uno.